2020
DOI: 10.30837/2522-9818.2020.11.156
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Requirements of International and National Standards for Measurement Methods and Metrological Equipment

Abstract: The subject of research in the article are methods and means of measurement and testing. The goal of the work is to analyze the metrological requirements of the ISO/IEC 17025:2017 standard for equipment and methods used to conduct tests in laboratories to ensure control of the metrological system processes, and to provide information on the practical application of the requirements of this standard, taking into account the provisions of other international standards. The following tasks are solved in the artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…It was suggested that customers should be involved within the development phases of a product/service, which includes Idea Generation, Concept Development, Product Design, Prototyping/Testing, and Maintenance. At each different stage, value is created collaboratively as organizations gain insight into customer preferences and ideas based on continuous interaction and feedback from costumers [59,60]. Important technological factors such as "collaboration system", "CRM Technology Infrastructure" and "Knowledge Map" facilitate absorbing, storing, organizing, and distributing customer knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that customers should be involved within the development phases of a product/service, which includes Idea Generation, Concept Development, Product Design, Prototyping/Testing, and Maintenance. At each different stage, value is created collaboratively as organizations gain insight into customer preferences and ideas based on continuous interaction and feedback from costumers [59,60]. Important technological factors such as "collaboration system", "CRM Technology Infrastructure" and "Knowledge Map" facilitate absorbing, storing, organizing, and distributing customer knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Standards organizations such as the International Organization for Standardization (ISO) and national metrology institutes establish and maintain standards for measurement techniques, equipment, and terminology (Trishch, et al, 2020;Sharp, 1999). These standards provide guidelines for ensuring consistency, comparability, and interoperability in metrological practices across industries and regions.…”
Section: Fundamentals Of Precision Metrologymentioning
confidence: 99%
“…In this investigation, the object of investigation is accredited calibration laboratories by the National Accreditation Committee in Indonesia (KAN). In implementation of ISO/IEC 17025:2017 for accredited calibration laboratories, one of the important factors is metrological traceability [2]. Metrological traceability is inherent entity, which determines the validity calibration result.…”
Section: Introductionmentioning
confidence: 99%